Open Access

Note on certain inequalities for Neuman means

  • Shu-Bo Chen1,
  • Zai-Yin He2,
  • Yu-Ming Chu1Email author,
  • Ying-Qing Song1 and
  • Xiao-Jing Tao3
Journal of Inequalities and Applications20142014:370

https://doi.org/10.1186/1029-242X-2014-370

Received: 21 May 2014

Accepted: 3 September 2014

Published: 25 September 2014

Abstract

In this paper, we give the explicit formulas for the Neuman means N A H , N H A , N A C , and N C A , and present the best possible upper and lower bounds for these means in terms of the combinations of harmonic mean H, arithmetic mean A, and contraharmonic mean C.

MSC:26E60.

Keywords

Schwab-Borchardt mean Neuman mean harmonic mean arithmetic mean contraharmonic mean

1 Introduction

Let a , b , c 0 with a b + a c + b c 0 . Then the symmetric integral R F ( a , b , c ) [1] of the first kind is defined as
R F ( a , b , c ) = 1 2 0 [ ( t + a ) ( t + b ) ( t + c ) ] 1 / 2 d t .
The degenerate case of R F , denoted by R C , plays an important role in the theory of special functions [1, 2], which is given by
R C ( a , b ) = R F ( a , b , b ) .
For a , b > 0 with a b , the Schwab-Borchardt mean SB ( a , b ) [35] of a and b is given by
SB ( a , b ) = { b 2 a 2 cos 1 ( a / b ) , a < b , a 2 b 2 cosh 1 ( a / b ) , a > b ,

where cos 1 ( x ) and cosh 1 ( x ) = log ( x + x 2 1 ) are the inverse cosine and inverse hyperbolic cosine functions, respectively.

Carlson [6] (see also [[7], (3.21)]) proved that
SB ( a , b ) = [ R C ( a 2 , b 2 ) ] 1 .

Recently, the Schwab-Borchardt mean has been the subject of intensive research. In particular, many remarkable inequalities for the Schwab-Borchardt mean and its generated means can be found in the literature [35, 811].

Let a > b > 0 , v = ( a b ) / ( a + b ) ( 0 , 1 ) , p ( 0 , ) , q ( 0 , π / 2 ) , r ( 0 , log ( 2 + 3 ) ) , and s ( 0 , π / 3 ) be the parameters such that 1 / cosh ( p ) = cos ( q ) = 1 v 2 , cosh ( r ) = sec ( s ) = 1 + v 2 , H ( a , b ) = 2 a b / ( a + b ) , G ( a , b ) = a b , A ( a , b ) = ( a + b ) / 2 , Q ( a , b ) = ( a 2 + b 2 ) / 2 , and C ( a , b ) = ( a 2 + b 2 ) / ( a + b ) be, respectively, the harmonic, geometric, arithmetic, quadratic, and contraharmonic means of a and b, S A H ( a , b ) = SB [ A ( a , b ) , H ( a , b ) ] , S H A ( a , b ) = SB [ H ( a , b ) , A ( a , b ) ] , S A C ( a , b ) = SB [ A ( a , b ) , C ( a , b ) ] , S C A ( a , b ) = SB [ C ( a , b ) , A ( a , b ) ] . Then Neuman [10] gave the explicit formulas
S A H ( a , b ) = A ( a , b ) tanh ( p ) p , S H A ( a , b ) = A ( a , b ) sin q q ,
(1.1)
S C A ( a , b ) = A ( a , b ) sinh ( r ) r , S A C ( a , b ) = A ( a , b ) tan s s .
(1.2)
Very recently, Neuman [12] found a new mean N ( a , b ) derived from the Schwab-Borchardt mean as follows:
N ( a , b ) = 1 2 [ a + b 2 SB ( a , b ) ] .
(1.3)
Let N A H ( a , b ) = N [ A ( a , b ) , H ( a , b ) ] , N H A ( a , b ) = N [ H ( a , b ) , A ( a , b ) ] , N A G ( a , b ) = N [ A ( a , b ) , G ( a , b ) ] , N G A ( a , b ) = N [ G ( a , b ) , A ( a , b ) ] , N A C ( a , b ) = N [ A ( a , b ) , C ( a , b ) ] , N C A ( a , b ) = N [ C ( a , b ) , A ( a , b ) ] , N A Q ( a , b ) = N [ A ( a , b ) , Q ( a , b ) ] , and N Q A ( a , b ) = N [ Q ( a , b ) , A ( a , b ) ] be the Neuman means. Then Neuman [12] proved that
G ( a , b ) < N A G ( a , b ) < N G A ( a , b ) < A ( a , b ) < N Q A ( a , b ) < N A Q ( a , b ) < Q ( a , b )
for all a , b > 0 with a b , and the double inequalities
α 1 A ( a , b ) + ( 1 α 1 ) G ( a , b ) < N G A ( a , b ) < β 1 A ( a , b ) + ( 1 β 1 ) G ( a , b ) , α 2 Q ( a , b ) + ( 1 α 2 ) A ( a , b ) < N A Q ( a , b ) < β 2 Q ( a , b ) + ( 1 β 2 ) A ( a , b ) , α 3 A ( a , b ) + ( 1 α 3 ) G ( a , b ) < N A G ( a , b ) < β 3 A ( a , b ) + ( 1 β 3 ) G ( a , b ) , α 4 Q ( a , b ) + ( 1 α 4 ) A ( a , b ) < N Q A ( a , b ) < β 4 Q ( a , b ) + ( 1 β 4 ) A ( a , b )

hold for all a , b > 0 with a b if and only if α 1 2 / 3 , β 1 π / 4 , α 2 2 / 3 , β 2 ( π 2 ) / [ 4 ( 2 1 ) ] = 0.689  , α 3 1 / 3 , β 3 1 / 2 , α 4 1 / 3 , and β 4 [ log ( 1 + 2 ) + 2 2 ] / [ 2 ( 2 1 ) ] = 0.356  .

Zhang et al. [13] presented the best possible parameters α 1 , α 2 , β 1 , β 2 [ 0 , 1 / 2 ] and α 3 , α 4 , β 3 , β 4 [ 1 / 2 , 1 ] such that the double inequalities
G ( α 1 a + ( 1 α 1 ) b , α 1 b + ( 1 α 1 ) a ) < N A G ( a , b ) < G ( β 1 a + ( 1 β 1 ) b , β 1 b + ( 1 β 1 ) a ) , G ( α 2 a + ( 1 α 2 ) b , α 2 b + ( 1 α 2 ) a ) < N G A ( a , b ) < G ( β 2 a + ( 1 β 2 ) b , β 2 b + ( 1 β 2 ) a ) , Q ( α 3 a + ( 1 α 3 ) b , α 3 b + ( 1 α 3 ) a ) < N Q A ( a , b ) < Q ( β 3 a + ( 1 β 3 ) b , β 3 b + ( 1 β 3 ) a ) , Q ( α 4 a + ( 1 α 4 ) b , α 4 b + ( 1 α 4 ) a ) < N A Q ( a , b ) < Q ( β 4 a + ( 1 β 4 ) b , β 4 b + ( 1 β 4 ) a )

hold for all a , b > 0 with a b .

In [14], the authors found the greatest values α 1 , α 2 , α 3 , α 4 , α 5 , α 6 , α 7 , α 8 , and the least values β 1 , β 2 , β 3 , β 4 , β 5 , β 6 , β 7 , β 8 such that the double inequalities
A α 1 ( a , b ) G 1 α 1 ( a , b ) < N G A ( a , b ) < A β 1 ( a , b ) G 1 β 1 ( a , b ) , α 2 G ( a , b ) + 1 α 2 A ( a , b ) < 1 N G A ( a , b ) < β 2 G ( a , b ) + 1 β 2 A ( a , b ) , A α 3 ( a , b ) G 1 α 3 ( a , b ) < N A G ( a , b ) < A β 3 ( a , b ) G 1 β 3 ( a , b ) , α 4 G ( a , b ) + 1 α 4 A ( a , b ) < 1 N A G ( a , b ) < β 4 G ( a , b ) + 1 β 4 A ( a , b ) , Q α 5 ( a , b ) A 1 α 5 ( a , b ) < N A Q ( a , b ) < Q β 5 ( a , b ) A 1 β 5 ( a , b ) , α 6 A ( a , b ) + 1 α 6 Q ( a , b ) < 1 N A Q ( a , b ) < β 6 A ( a , b ) + 1 β 6 Q ( a , b ) , Q α 7 ( a , b ) A 1 α 7 ( a , b ) < N Q A ( a , b ) < Q β 7 ( a , b ) A 1 β 7 ( a , b ) , α 8 A ( a , b ) + 1 α 8 Q ( a , b ) < 1 N Q A ( a , b ) < β 8 A ( a , b ) + 1 β 8 Q ( a , b )

hold for all a , b > 0 with a b .

The main purpose of this paper is to give the explicit formulas for the Neuman means N A H , N H A , N A C , and N C A , and to present the best possible upper and lower bounds for these means in terms of the combinations of harmonic, arithmetic, and contraharmonic means. Our main results are Theorems 1.1-1.3.

Theorem 1.1 Let a > b > 0 , v = ( a b ) / ( a + b ) ( 0 , 1 ) , p ( 0 , ) , q ( 0 , π / 2 ) , r ( 0 , log ( 2 + 3 ) ) , and s ( 0 , π / 3 ) be the parameters such that 1 / cosh ( p ) = cos ( q ) = 1 v 2 , cosh ( r ) = sec ( s ) = 1 + v 2 . Then we have
N A H ( a , b ) = 1 2 A ( a , b ) [ 1 + 2 p sinh ( 2 p ) ] ,
(1.4)
N H A ( a , b ) = 1 2 A ( a , b ) [ cos ( q ) + q sin ( q ) ] ,
(1.5)
N C A ( a , b ) = 1 2 A ( a , b ) [ cosh ( r ) + r sinh ( r ) ] ,
(1.6)
N A C ( a , b ) = 1 2 A ( a , b ) [ 1 + 2 s sin ( 2 s ) ] ,
(1.7)
and
H ( a , b ) < N A H ( a , b ) < N H A ( a , b ) < A ( a , b ) < N C A ( a , b ) < N A C ( a , b ) < C ( a , b ) .
(1.8)
Theorem 1.2 The double inequalities
α 1 A ( a , b ) + ( 1 α 1 ) H ( a , b ) < N A H ( a , b ) < β 1 A ( a , b ) + ( 1 β 1 ) H ( a , b ) ,
(1.9)
α 2 A ( a , b ) + ( 1 α 2 ) H ( a , b ) < N H A ( a , b ) < β 2 A ( a , b ) + ( 1 β 2 ) H ( a , b ) ,
(1.10)
α 3 C ( a , b ) + ( 1 α 3 ) A ( a , b ) < N C A ( a , b ) < β 3 C ( a , b ) + ( 1 β 3 ) A ( a , b ) ,
(1.11)
α 4 C ( a , b ) + ( 1 α 4 ) A ( a , b ) < N A C ( a , b ) < β 4 C ( a , b ) + ( 1 β 4 ) A ( a , b )
(1.12)

hold for all a , b > 0 with a b if and only if α 1 1 / 3 , β 1 1 / 2 , α 2 2 / 3 , β 2 π / 4 = 0.7853  , α 3 1 / 3 , β 3 3 log ( 2 + 3 ) / 6 = 0.3801  , α 4 2 / 3 , and β 4 ( 4 3 π 9 ) / 18 = 0.7901  .

Theorem 1.3 The double inequalities
α 5 H ( a , b ) + 1 α 5 A ( a , b ) < 1 N A H ( a , b ) < β 5 H ( a , b ) + 1 β 5 A ( a , b ) ,
(1.13)
α 6 H ( a , b ) + 1 α 6 A ( a , b ) < 1 N H A ( a , b ) < β 6 H ( a , b ) + 1 β 6 A ( a , b ) ,
(1.14)
α 7 A ( a , b ) + 1 α 7 C ( a , b ) < 1 N C A ( a , b ) < β 7 A ( a , b ) + 1 β 7 C ( a , b ) ,
(1.15)
α 8 A ( a , b ) + 1 α 8 C ( a , b ) < 1 N A C ( a , b ) < β 8 A ( a , b ) + 1 β 8 C ( a , b ) ,
(1.16)

hold for all a , b > 0 with a b if and only if α 5 0 , β 5 2 / 3 , α 6 0 , β 6 1 / 3 , α 7 [ 2 3 log ( 2 + 3 ) ] / [ 2 3 + log ( 2 + 3 ) ] = 0.4490  , β 7 2 / 3 , α 8 ( 9 3 4 π ) / ( 3 3 + 4 π ) = 0.1701  , and β 8 1 / 3 .

2 Lemmas

In order to prove our main results we need several lemmas, which we present in this section.

Lemma 2.1 (See [[15], Theorem 1.25])

For < a < b < , let f , g : [ a , b ] R be continuous on [ a , b ] , and be differentiable on ( a , b ) , let g ( x ) 0 on ( a , b ) . If f ( x ) / g ( x ) is increasing (decreasing) on ( a , b ) , then so are
f ( x ) f ( a ) g ( x ) g ( a ) and f ( x ) f ( b ) g ( x ) g ( b ) .

If f ( x ) / g ( x ) is strictly monotone, then the monotonicity in the conclusion is also strict.

Lemma 2.2 (See [[16], Lemma 1.1])

Suppose that the power series f ( x ) = n = 0 a n x n and g ( x ) = n = 0 b n x n have the radius of convergence r > 0 and a n , b n > 0 for all n 0 . If the sequence { a n / b n } is (strictly) increasing (decreasing) for all n 0 , then the function f ( x ) / g ( x ) is also (strictly) increasing (decreasing) on ( 0 , r ) .

Lemma 2.3 (See [[12], Theorem 4.1])

If a > b , then
N ( b , a ) > N ( a , b ) .
Lemma 2.4 The function
φ 1 ( t ) = sinh ( 2 t ) 4 sinh ( t ) + 2 t sinh ( 2 t ) 2 sinh ( t )

is strictly increasing from ( 0 , ) onto ( 2 / 3 , 1 ) .

Proof Making use of power series expansion we get
φ 1 ( t ) = n = 1 2 2 n + 1 4 ( 2 n + 1 ) ! t 2 n + 1 n = 1 2 2 n + 1 2 ( 2 n + 1 ) ! t 2 n + 1 = n = 0 2 2 n + 3 4 ( 2 n + 3 ) ! t 2 n n = 0 2 2 n + 3 2 ( 2 n + 3 ) ! t 2 n .
(2.1)
Let
a n = 2 2 n + 3 4 ( 2 n + 3 ) ! , b n = 2 2 n + 3 2 ( 2 n + 3 ) ! .
(2.2)
Then
a n > 0 , b n > 0 ,
(2.3)

and a n / b n = 1 1 / ( 2 2 n + 2 1 ) is strictly increasing for all n 0 .

Note that
φ 1 ( 0 + ) = a 0 b 0 = 2 3 , φ 1 ( ) = lim n a n b n = 1 .
(2.4)

Therefore, Lemma 2.4 follows easily from Lemma 2.2 and (2.1)-(2.4) together with the monotonicity of the sequence { a n / b n } . □

Lemma 2.5 The function
φ 2 ( t ) = 2 t sin ( 2 t ) sin t ( 1 cos t )

is strictly increasing from ( 0 , π / 2 ) onto ( 8 / 3 , π ) .

Proof Let f 1 ( t ) = 2 t sin ( 2 t ) and g 1 ( t ) = sin t ( 1 cos t ) . Then simple computations lead to
φ 2 ( t ) = f 1 ( t ) f 1 ( 0 ) g 1 ( t ) g 1 ( 0 )
(2.5)

and f 1 ( t ) / g 1 ( t ) = 4 [ 1 1 / ( 2 + 1 / cos t ) ] is strictly increasing on ( 0 , π / 2 ) .

Note that
φ 2 ( 0 + ) = lim t 0 + f 1 ( t ) g 1 ( t ) = 8 3 , φ 2 ( π / 2 ) = π .
(2.6)

Therefore, Lemma 2.5 follows from Lemma 2.1, (2.5), (2.6), and the monotonicity of f 1 ( t ) / g 1 ( t ) . □

Lemma 2.6 The function
φ 3 ( t ) = sinh ( t ) cosh ( t ) t [ sinh ( t ) cosh ( t ) + t ] ( cosh ( t ) 1 )

is strictly decreasing from ( 0 , ) onto ( 0 , 2 / 3 ) .

Proof Simple computations lead to
φ 3 ( t ) = 2 sinh ( 2 t ) 4 t sinh ( 3 t ) + 4 t cosh ( t ) + sinh ( t ) 2 sinh ( 2 t ) 4 t = n = 0 2 2 n + 4 ( 2 n + 3 ) ! t 2 n n = 0 3 2 n + 3 2 2 n + 4 + 8 n + 13 ( 2 n + 3 ) ! t 2 n .
(2.7)
Let
a n = 2 2 n + 4 ( 2 n + 3 ) ! , b n = 3 2 n + 3 2 2 n + 4 + 8 n + 13 ( 2 n + 3 ) ! .
(2.8)
Then
a n > 0 , b n > 0 ,
(2.9)
and
a n + 1 b n + 1 a n b n = 2 2 n + 4 ( 5 × 3 2 n + 3 24 n 31 ) ( 3 2 n + 5 2 2 n + 6 + 8 n + 21 ) ( 3 2 n + 3 2 2 n + 4 + 8 n + 13 ) < 0
(2.10)

for all n 0 .

Note that
φ 3 ( 0 + ) = a 0 b 0 = 2 3 , φ 3 ( ) = lim n a n b n = 0 .
(2.11)

Therefore, Lemma 2.6 follows easily from (2.7)-(2.11) and Lemma 2.2. □

Lemma 2.7 The function
f ( t ) = 9 cos t + t sin t

is strictly decreasing on the interval ( 0 , π / 2 ) .

Proof Let f 2 ( t ) = 9 sin t cos t + t and g 2 ( t ) = sin t . Then simple computations lead to
f ( t ) = f 2 ( t ) f 2 ( 0 ) g 2 ( t ) g 2 ( 0 ) , f 2 ( t ) g 2 ( t ) = 18 cos 2 t 8 cos t ,
(2.12)
and
[ f 2 ( t ) g 2 ( t ) ] = 2 sin t ( 9 cos 2 t + 4 ) cos 2 t < 0
(2.13)

for t ( 0 , π / 2 ) .

Therefore, Lemma 2.7 follows easily from (2.12) and (2.13) together with Lemma 2.1. □

Lemma 2.8 The function
φ 4 ( t ) = sin t cos t t ( t + sin t cos t ) ( 1 cos t )

is strictly decreasing from ( 0 , π / 2 ) onto ( 1 , 2 / 3 ) .

Proof Let f 3 ( t ) = sin t cos t t and g 3 ( t ) = ( t + sin t cos t ) ( 1 cos t ) . Then simple computations lead to
φ 4 ( t ) = f 3 ( t ) g 3 ( t ) = f 3 ( t ) f 3 ( 0 ) g 3 ( t ) g 3 ( 0 ) ,
(2.14)
f 3 ( t ) g 3 ( t ) = f 3 ( t ) f 3 ( 0 ) g 3 ( t ) g 3 ( 0 ) ,
(2.15)
and
f 3 ( t ) g 3 ( t ) = 4 4 ( 9 cos t + t sin t ) .
(2.16)
Note that
φ 4 ( 0 + ) = lim t 0 + f 3 ( t ) g 3 ( t ) = 2 3 , φ 4 ( π 2 ) = 1 .
(2.17)

Therefore, Lemma 2.8 follows from Lemma 2.1 and Lemma 2.7 together with (2.14)-(2.17). □

3 Proofs of Theorems 1.1-1.3

Proof of Theorem 1.1 It follows from (1.1)-(1.3) as we clearly see that
N A H ( a , b ) = 1 2 [ A ( a , b ) + H 2 ( a , b ) S A H ( a , b ) ] = 1 2 A ( a , b ) [ 1 + ( 1 v 2 ) 2 p tanh ( p ) ] = 1 2 A ( a , b ) [ 1 + p tanh ( p ) cosh 2 ( p ) ] = 1 2 A ( a , b ) [ 1 + 2 p sinh ( 2 p ) ] , N H A ( a , b ) = 1 2 [ H ( a , b ) + A 2 ( a , b ) S H A ( a , b ) ] = 1 2 A ( a , b ) [ ( 1 v 2 ) + q sin q ] = 1 2 A ( a , b ) [ cos q + q sin q ] , N C A ( a , b ) = 1 2 [ C ( a , b ) + A 2 ( a , b ) S C A ( a , b ) ] = 1 2 A ( a , b ) [ ( 1 + v 2 ) + r sinh ( r ) ] = 1 2 A ( a , b ) [ cosh ( r ) + r sinh ( r ) ] , N A C ( a , b ) = 1 2 [ A ( a , b ) + C 2 ( a , b ) S A C ( a , b ) ] = 1 2 A ( a , b ) [ 1 + ( 1 + v 2 ) 2 s tan ( s ) ] = 1 2 A ( a , b ) [ 1 + s tan ( s ) cos 2 s ] = 1 2 A ( a , b ) [ 1 + 2 s sin ( 2 s ) ] .

Inequalities (1.8) follow easily from H ( a , b ) < A ( a , b ) < C ( a , b ) and Lemma 2.3 together with the fact that N K L ( a , b ) is a mean of K ( a , b ) and L ( a , b ) for K ( a , b ) , L ( a , b ) { H ( a , b ) , A ( a , b ) , C ( a , b ) } . □

Proof of Theorem 1.2 Without loss of generality, we assume that a > b . Let v = ( a b ) / ( a + b ) ( 0 , 1 ) , p ( 0 , ) , q ( 0 , π / 2 ) , r ( 0 , log ( 2 + 3 ) ) , and s ( 0 , π / 3 ) be the parameters such that 1 / cosh ( p ) = cos ( q ) = 1 v 2 , cosh ( r ) = sec ( s ) = 1 + v 2 . Then from (1.4)-(1.7) we have
N A H ( a , b ) H ( a , b ) A ( a , b ) H ( a , b ) = [ 1 + 2 p / sinh ( 2 p ) ] / 2 ( 1 v 2 ) v 2 = [ 1 + 2 p / sinh ( 2 p ) ] / 2 1 / cosh ( p ) 1 1 / cosh ( p ) = φ 1 ( p ) ,
(3.1)
N H A ( a , b ) H ( a , b ) A ( a , b ) H ( a , b ) = [ cos q + q / sin q ] / 2 ( 1 v 2 ) v 2 = [ cos q + q / sin q ] / 2 cos q 1 cos q = 1 4 φ 2 ( q ) ,
(3.2)
N C A ( a , b ) A ( a , b ) C ( a , b ) A ( a , b ) = [ cosh ( r ) + r / sinh ( r ) ] / 2 1 v 2 = [ cosh ( r ) + r / sinh ( r ) ] / 2 1 cosh ( r ) 1 = 1 2 φ 1 ( r ) ,
(3.3)
N A C ( a , b ) A ( a , b ) C ( a , b ) A ( a , b ) = [ 1 + 2 s / sin ( 2 s ) ] / 2 1 v 2 = [ 1 + 2 s / sin ( 2 s ) ] / 2 1 sec ( s ) 1 = 1 4 φ 2 ( s ) ,
(3.4)

where the functions φ 1 and φ 2 are defined as in Lemmas 2.4 and 2.5, respectively.

Note that
φ 1 [ log ( 2 + 3 ) ] = 3 log ( 2 + 3 ) / 6
(3.5)
and
φ 2 ( π 3 ) = 8 3 π 18 9 .
(3.6)

Therefore, inequality (1.9) holds for all a , b > 0 with a b if and only if α 1 1 / 3 and β 1 1 / 2 follows from (3.1) and Lemma 2.4, inequality (1.10) holds for all a , b > 0 with a b if and only if α 2 2 / 3 and β 2 π / 4 follows from (3.2) and Lemma 2.5, inequality (1.11) holds for all a , b > 0 with a b if and only if α 3 1 / 3 and β 3 3 log ( 2 + 3 ) / 6 follows from (3.3) and (3.5) together with Lemma 2.4, and inequality (1.12) holds for all a , b > 0 with a b if and only if α 4 2 / 3 and β 4 ( 4 3 π 9 ) / 18 follows from (3.4) and (3.6) together with Lemma 2.5. □

Proof of Theorem 1.3 Without loss of generality, we assume that a > b . Let v = ( a b ) / ( a + b ) ( 0 , 1 ) , p ( 0 , ) , q ( 0 , π / 2 ) , r ( 0 , log ( 2 + 3 ) ) , and s ( 0 , π / 3 ) be the parameters such that 1 / cosh ( p ) = cos ( q ) = 1 v 2 , cosh ( r ) = sec ( s ) = 1 + v 2 . Then from (1.4)-(1.7) we have
1 / N A H ( a , b ) 1 / A ( a , b ) 1 / H ( a , b ) 1 / A ( a , b ) = 2 1 + 2 p / sinh ( 2 p ) 1 1 1 v 2 1 = 2 sinh ( 2 p ) 2 p + sinh ( 2 p ) 1 cosh ( p ) 1 = φ 3 ( p ) ,
(3.7)
1 / N H A ( a , b ) 1 / A ( a , b ) 1 / H ( a , b ) 1 / A ( a , b ) = 2 cos ( q ) + q / sin ( q ) 1 1 1 v 2 1 = 2 sin ( q ) sin ( q ) cos ( q ) q sin ( q ) cos ( q ) + q 1 cos ( q ) cos ( q ) = 1 + φ 4 ( q ) ,
(3.8)
1 / N C A ( a , b ) 1 / C ( a , b ) 1 / A ( a , b ) 1 / C ( a , b ) = 2 cosh ( r ) + r / sinh ( r ) 1 1 + v 2 1 1 1 + v 2 = φ 3 ( r ) ,
(3.9)
and
1 / N A C ( a , b ) 1 / C ( a , b ) 1 / A ( a , b ) 1 / C ( a , b ) = 1 + φ 4 ( s ) ,
(3.10)

where the functions φ 3 and φ 4 are defined as in Lemmas 2.6 and 2.8, respectively.

Note that
φ 3 [ log ( 2 + 3 ) ] = 2 3 log ( 2 + 3 ) 2 3 + log ( 2 + 3 )
(3.11)
and
φ 4 ( π 3 ) = 8 π 6 3 4 π + 3 3 .
(3.12)

Therefore, Theorem 1.3 follows easily from (3.7)-(3.12) together with Lemmas 2.6 and 2.8. □

Declarations

Acknowledgements

This research was supported by the Natural Science Foundation of China under Grants 61374086, 11371125, and 11401192, the Natural Science Foundation of Hunan Province under Grant 12C0577, and the Research Foundation of Education Bureau of Hunan Province under Grant 14A026.

Authors’ Affiliations

(1)
School of Mathematics and Computation Science, Hunan City University
(2)
Department of Mathematics, Huzhou Teachers College
(3)
School of Mathematics and Econometrics, Hunan University

References

  1. Carlson BC: Special Functions of Applied Mathematics. Academic Press, New York; 1977.MATHGoogle Scholar
  2. Carlson BC, Gustafson JL: Asymptotic approximations for symmetric elliptic integrals. SIAM J. Math. Anal. 1994,25(2):288-303. 10.1137/S0036141092228477MathSciNetView ArticleMATHGoogle Scholar
  3. Neuman E, Sándor J: On the Schwab-Borchardt mean. Math. Pannon. 2003,14(2):253-266.MathSciNetMATHGoogle Scholar
  4. Neuman E, Sándor J: On the Schwab-Borchardt mean II. Math. Pannon. 2006,17(1):49-59.MathSciNetMATHGoogle Scholar
  5. Neuman E: Inequalities for the Schwab-Borchardt mean and their applications. J. Math. Inequal. 2011,5(4):601-609.MathSciNetView ArticleMATHGoogle Scholar
  6. Carlson BC: Algorithms involving arithmetic and geometric means. Am. Math. Mon. 1971, 78: 496-505. 10.2307/2317754View ArticleMathSciNetMATHGoogle Scholar
  7. Brenner JL, Carlson BC: Homogeneous mean values: weights and asymptotics. J. Math. Anal. Appl. 1987,123(1):265-280. 10.1016/0022-247X(87)90308-8MathSciNetView ArticleMATHGoogle Scholar
  8. He Z-Y, Chu Y-M, Wang M-K: Optimal bounds for Neuman means in terms of harmonic and contraharmonic means. J. Appl. Math. 2013. Article ID 807623, 2013: Article ID 807623Google Scholar
  9. Chu Y-M, Qian W-Q: Refinements of bounds for Neuman means. Abstr. Appl. Anal. 2014. Article ID 354132, 2014: Article ID 354132Google Scholar
  10. Neuman E: On some means derived from the Schwab-Borchardt mean. J. Math. Inequal. 2014,8(1):171-183.MathSciNetView ArticleMATHGoogle Scholar
  11. Neuman E: On some means derived from the Schwab-Borchardt mean II. J. Math. Inequal. 2014,8(2):361-370.MathSciNetMATHGoogle Scholar
  12. Neuman E: On a new bivariate mean. Aequ. Math. 2013. 10.1007/s00010-013-0224-8Google Scholar
  13. Zhang Y, Chu Y-M, Jiang Y-L: Sharp geometric mean bounds for Neuman means. Abstr. Appl. Anal. 2014. Article ID 949815, 2014: Article ID 949815Google Scholar
  14. arXiv: Guo, Z-J, Zhang, Y, Chu, Y-M, Song, Y-Q: Sharp bounds for Neuman means in terms of geometric, arithmetic and quadratic means. arXiv:1405.4384v1 arXiv:1405.4384v1
  15. Anderson GD, Qiu S-L, Vamanamurthy MK, Vuorinen M: Generalized elliptic integrals and modular equations. Pac. J. Math. 2000,192(1):1-37. 10.2140/pjm.2000.192.1MathSciNetView ArticleGoogle Scholar
  16. Simić S, Vuorinen M: Landen inequalities for zero-balanced hypergeometric functions. Abstr. Appl. Anal. 2012. Article ID 932061, 2012: Article ID 932061Google Scholar

Copyright

© Chen et al.; licensee Springer. 2014

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited.